Systematic Literature-Review: Analisis Komparasi Media Sosial dalam Penyebaran Informasi - Septian, Gilang Dwi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The development of technology, digital media, and social media is inversely proportional to the low level of digital literacy in society. When the use of these media is not wise, the information conveyed within them can be misleading. This study aims to analyze the differences in the influence of information dissemination on the social media platforms Instagram and Whatsapp. The method used in this research is a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. From all the literature that has been reviewed, it is broadly concluded that social media, particularly Instagram and Whatsapp, have a significant influence, albeit with different scales, targets, and methods of delivery.